Patients with substance use disorders receiving continued care in skilled nursing facilities following hospitalization. Issue 1 (1st December 2022) - Mitchell, Shannon Gwin; Nordeck, Courtney D.; Lertch, Elizabeth; Ross, Tyler E.; Welsh, Christopher; Schwartz, Robert P.; Gryczynski, Jan
Abstract: Background: As hospitals in the US face pressures to reduce lengths of stay, healthcare systems are increasingly utilizing skilled nursing facilities (SNFs) to continue treating patients stable enough to leave the hospital, but not to return home. Substance use disorder (SUD) can complicate care of patients transferred to SNFs. The objective of this paper is to understand SNF experiences for this population of patients with comorbid SUD transferred to SNFs and examine care experiences in these facilities. Methods: This secondary mixed-methods analysis focuses on SNF experiences from a clinical trial of patient navigation services for medically-hospitalized adults with comorbid opioid, cocaine, and/or alcohol use disorder. This study compared baseline assessments and medical record review for participants ( N = 400) with vs. without SNF transfer, and analyzed semi-structured qualitative interviews with a subsample of 15 participants purposively selected based on their transfer to a SNF. Results: Over 1 in 4 participants had a planned discharged to a SNF (26.8% sub-acute, 3.3% acute). Compared to participants with other types of discharge, participants discharged to a SNF had longer initial hospitalizations (4.9 vs. 11.8 days, p < 0.001), and were more likely to be White (38.6 vs. 50.8%; p = 0.02), female (38.9 vs. 52.5%; p = 0.01), have opioid use disorder (75.7 vs. 85.0%, p = 0.03), and be hospitalized for infection (43.6 vs. 58.3%; p = 0.007), and less likely to have worked prior to hospitalization (24.3 vs. 12.5%; p = 0.006). Qualitative narratives identified several themes from the SNF experience, including opioid analgesic dosing issues, challenges to the use of opioid agonist treatment of OUD, illicit opioid dealing/use, and limited access to addiction recovery support services during and following the SNF stay. Conclusions: SNFs are a common disposition for patients in need of subacute services following hospitalization but may be ill-equipped to properly manage patients in need of new or continuing SUD treatment.